Alumni affiliation 2023 / UiTM Sarawak (Perpustakaan Tun Abdul Razak, 2023)
This e-magazine is mainly focusing on Management of Business Records and how it is related to the Alumni as its core business. The Alumni can help with global admissions and recruitment efforts, career and professional development, local and state advocacy or lobbying and through their generous philanthropic support. All articles and write-ups included in this e-publication are based on research or non academic research of the university. The purpose of publishing this e-magazine is to strenghten the engagement of the alumni in university and how to strengthen this relationship so that we can create meaningful values in return to our graduates. One of the best parts of being part of an alumni association is the network that comes with it. An alumni network connects you, as a graduate, with a number of professional contacts and other graduates from your university.